Penerapan Teknik Realisme pada Film The Platform Sutradara Galder Gaztelu-Urrutia - Putri Ramadhani; Dani Manesah (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
The film The Platform (El Hoyo) tells the story of a vertical prison with a food distribution system that creates social and moral conflict among the prisoners. The creation of this film raises social issues such as injustice, greed and the struggle for survival with a realism approach, which seeks to present life as it is without manipulation. The creation method is based on the ideas of André Bazin, utilizing long takes, deep focus, detailed set design, natural acting and dim lighting to create an authentic atmosphere. This approach produces an immersive cinematic experience, presenting relevant and realistic symbolism for the viewer.